2006
DOI: 10.1530/rep.1.01049
|View full text |Cite
|
Sign up to set email alerts
|

Within and between breed differences in freezing tolerance and plasma membrane fatty acid composition of boar sperm

Abstract: The response of sperm to cryopreservation and the fertility of frozen -thawed semen varies between species. Besides species differences in sperm physiology, structure and biochemistry, factors such as sperm transport and female reproductive tract anatomy will affect fertility of frozen-thawed semen. Therefore, studying differences in sperm cryotolerance between breeds and individuals instead of between species may reveal sources of variability in sperm cryotolerance. In the present study, the effect of cooling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
101
0
9

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(121 citation statements)
references
References 30 publications
11
101
0
9
Order By: Relevance
“…The basic mechanisms of individual genetic differences connected with the susceptibility to damage induced by cryopreservation remain unknown, but they may be manifested in the varied biochemical composition of semen (Holt et al 2005). For example, Waterhouse et al (2006) stated that differences in individual sensitivity of boar spermatozoa to cryopreservation are connected with the amount of long-chain polyunsaturated fatty acids (PUFAs) contained in plasma membranes. Since boar spermatozoa are characterized by a high level of long-chain polyunsaturated fatty acids (PUFAs) and a low cholesterol level in membranes, they are particularly sensitive to cooling processes (Park andLynch 1992, Penny et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The basic mechanisms of individual genetic differences connected with the susceptibility to damage induced by cryopreservation remain unknown, but they may be manifested in the varied biochemical composition of semen (Holt et al 2005). For example, Waterhouse et al (2006) stated that differences in individual sensitivity of boar spermatozoa to cryopreservation are connected with the amount of long-chain polyunsaturated fatty acids (PUFAs) contained in plasma membranes. Since boar spermatozoa are characterized by a high level of long-chain polyunsaturated fatty acids (PUFAs) and a low cholesterol level in membranes, they are particularly sensitive to cooling processes (Park andLynch 1992, Penny et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The ratio of ∑ DPA and DHA/ ∑ all other membrane fatty acids was significantly related to survival rate (plasma membrane integrity) of sperm for both Norwegian Landrace and Duroc boars. Thus Waterhouse et al [11] concluded that male-tomale differences in sperm survival rate after freezing and thawing may be partly related to the amount of long-chain PUFA in the sperm plasma membranes.…”
Section: Boarmentioning
confidence: 99%
“…Lipid and fatty acid composition of sperm cells differ not only for different animals [7,8] but also for different species [9][10][11][12], even for fertile and subfertile population of same species [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The sperm suspensions were loaded into 0.5 mL polyvinyl chloride medium-straws (Bio-Vet, Fleurance, France) and sealed with plasticine. All straws were placed horizontally on a rack and put into a chamber of the controlledrate freezer set to +5ºC [19][20][21][22]. The cooling/freezing rate was as follows: 3ºC/min from +5ºC to −5ºC and 1 min of holding time and thereafter 50ºC/min from −5ºC to −140ºC.…”
Section: Semen Freezing Processmentioning
confidence: 99%